1993
DOI: 10.1128/jb.175.3.701-705.1993
|View full text |Cite
|
Sign up to set email alerts
|

Presence of two independent chromosomes in the Brucella melitensis 16M genome

Abstract: Mapping the restriction fragments of the Brucella melitensis 16M genome with a new restriction endonuclease, Pacl, which cut the DNA into only eight fragments, indicated that this species contains two unique and independent replicons of about 2,100 and 1,150 kb. Pulsed-field gel electrophoresis of intact DNA revealed two bands migrating the expected distances. These replicons were identified as two unique and independent chromosomes by the presence of rRNA operons and genes for heat shock proteins mapping to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 19 publications
3
61
0
2
Order By: Relevance
“…Similarity among the Brucella orthologs was high, with an average amino acid sequence identity of greater than 99%. The B. abortus sequence confirmed PFGE maps (27) with regard to genome size, chromosome number, and presence of an inversion described in Chr II relative to other genomes.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Similarity among the Brucella orthologs was high, with an average amino acid sequence identity of greater than 99%. The B. abortus sequence confirmed PFGE maps (27) with regard to genome size, chromosome number, and presence of an inversion described in Chr II relative to other genomes.…”
Section: Resultsmentioning
confidence: 62%
“…genomes are composed of two circular chromosomes of approximately 2.1 and 1.2 Mbp (22,27,28), with the exception of B. suis biovar 3, which has a single chromosome of 3.1 Mbp. PFGE studies revealed other differences, including a 640-kb inversion in the small chromosome of B. abortus 544 and a deletion in the small chromosome of B. ovis.…”
mentioning
confidence: 99%
“…Brucella genus is classified phylogenetically within the α2 subdivision of Proteobacteria which comprises of Agrobacterium, Bartonella, Ochrobactrum, Rhizobium, Rhodobacter, and Rickettsia (Moreno et al, 1990). Genome of B. abortus has two circular chromosomes of 2.1 Mb and 1.5 Mb size without plasmids (Michaux et al, 1993;MichauxCharachon et al, 1997). Recent years has seen the completion of genome of B. abortus (Sanchez et al, 2001), B. melitensis (GenBank NC 003317 and NC 003318) (DelVecchio et al, 2002) and B. suis (GenBank NC 002969) thus increasing the opportunity for understanding the pathogenicity of Brucella.…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria, such as Borrelia burgdorferi and Rhodococcus fascians, have linear chromosomes (4,20,24), whereas Streptomyces lividans and Streptomyces coelicolor have linear chromosomes that may become circular as a result of deletions spanning both telomeres (34,35). Still others, such as Brucella melitensis and Leptospira interrogans, have segmented genomes (40,63). The segmented genome of Agrobacterium tumefaciens has one circular and one linear component (1).…”
mentioning
confidence: 99%